Centro cultural pueblo de Usme (2021)
The project focuses on designing a cultural facility in the fifth town of Usme, which preserves the cultural and historical heritage, such as the indigenous archaeological find, the colonial architecture and its lakes that the sector contemplates. The development of the project includes two types of research, analytics and recognition of the area. In this way, a variety of information and data crossing are obtained, which guides the equipment towards social and cultural integration.